Mathematical model of optimization of preventive maintenance of transmitting active phased antenna arrangements of multifunctional radars - Костановський, Валерій Вікторович; Мачалін, Ігор Олексійович (Science-based technologies, 2020)
In the article, the authors discuss the issues of determining the reliability indicators and maintenance of transmitting active phased array antennas (AFAR) of multifunctional radars. The analysis of the existing models of reliability and maintenance of AFAR radar. It is shown that the most interesting models of transmitting AFAR reliability are the reliability model with a two-level block diagram of the AFAR and the reliability model according to the criterion of permissible reduction of the maximum radar range. Among the AFAR maintenance models, the most interesting ones were identified: the AFAR optimal preventive maintenance (ON) model with a single-level structure and the AFAR maintenance model by technical condition. Using the results of the analysis, models of reliability and optimal preventive maintenance of a multi-functional radar transmitting AFAR are constructed. The analytical expressions of the reliability indicators of a two-level AFAR are presented: the average operating time to failure and the probabilities of failure-free operation of the antenna transmitting sublattice and the transmitting AFAR as a whole. Analytical expressions are constructed for the criteria for the effectiveness of optimal software (coefficient of technical use and mathematical expectation of specific operating costs) and the criteria for gaining from software optimization. The work considers an illustrative example of calculating the reliability and optimal software of a two-level AFAR, including 6400 microwave emitting channels, arranged in 100 sublattices with 64 channels each. The mean operating time to failure and the optimal periodicity of the AFAR software were determined for three versions of the reliability indicators of the emitting channels. The graphs of the probability of failure-free operation, the coefficient of technical use and the mathematical expectation of the specific operational costs of the AFAR were constructed and analyzed. The values of the optimal periodicity and the gain from optimization are obtained. It is shown that the results of optimal software should be used at the initial stage of operation of radars with AFAR — at the stage of warranty service. At further stages of operation - the stages of post-warranty service, it is recommended to use the AFAR maintenance method according to the technical condition. The models proposed by the authors can be useful to engineers and scientists developing radars with AFAR and employees of operating organizations.